PENGARUH TAYANGAN BOYBAND BTS DI APLIKASI VLIVE TERHADAP PERILAKU IMITASI PADA KOMUNITAS MEDIA SOSIAL LINE ARMY RIAU - Shinta Seftiani; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Vlive application is an application with the main features of live broadcast from South Korean idols. This application brings idols and fans together virtually all over the world. In the Vlive application there are several channels that can be seen from South Korean idols and followed by K-Pop fans. The current most followed channel on the Vlive application is a channel from the boyband BTS. In the show on Vlive application, fans can see how the daily avtivities of BTS members, ranging from behavior, appearance to goods or products used by BTS members who usually always become a conversation among fans and often they also imitate it in daily activities. The purpose of this study was to analyze how much influence of boyband BTS shows on the Vlive application on imitation behavior on fans.In this study, researchers used Stimulus- Response Theory (SR) and Social Learning Theory. The method used in this study is quantitative explanatory with random sampling techniques. The population in this study was 217 people with a samples of 141 respondents. Data collection techniques in this study used a questionnaire, to find out the effect between two variables, the writer uses simple linear regression analysis. Furthermore, data testing was performed using the SPSS program for windows version 21.Based on the results of simple linear regression, the regression coefficient values obtained in this study were Y = 23,041 + 2,015 X with a significance level of 0,000. The significance level is smaller than α = 0.05, which means Ho rejected and Ha accepted, with the statement that there are significant shows boyband BTS on the Vlive app on imitation behavior on Riau Army line social media. The coefficient of determination (R2) in the study of 41.7% which means these figures show that the effect ofimpressions boyband base stations in the VLive application against imitation behavior on social media line Army Lists included in the medium category. While the remaining 58.3% is influenced by other variables not included in this study.